Implementation Lessons Learned : EITI Policy Implications - Darby, Sefton; Ravat, Anwar (World Bank, Washington, DC, 2013)
This study was undertaken as a desk review, commissioned by the World Bank (WB), and is focused on areas of the Extractive Industries Transparency Initiative (EITI) policy, which have proven unclear or difficult for implementing countries. This report is designed to collate the key EITI policy implications which the Policy and Operations Unit (COCPO) team had identified through its work with EITI countries, and from EITI implementation experience. The review seeks to emphasize best practices, identify common constraints, and highlight results and issues emerging from EITI countries, and the most recent EITI implementation and reporting cycles. The report aims to make incremental suggestions to build on this record of achievement and help maintain broad policy consistency. In particular the report recognizes that it is easier to suggest policy changes than actually carry them out, and it is for this reason that the report makes most of its suggestions in areas where policy requires clarification and refinement, in order to make the implementation process in countries more efficient and less focused on unhelpful debates on points of interpretation. It suggests areas where EITI policy might be revised for clarity, and provides recommendations concerning policy and implementation management.